Gerontological social work : a task-centered approach - Naleppa, Matthias J.; Reid, William James, 1928- (New York : Columbia University Press, 2003)
"Gerontological Social Work features in-depth coverage of specific client problems, such as physical or mental health, caregiving, home and personal safety, senior living, and long-term care arrangements. A series of task planners offer a menu of possible actions that can resolve or alleviate a designated problem. Rating scales, schedules, and other forms assist the practitioner and client in the intervention process. An appendix classified by topic lists hundreds of Web sites related to work with the elderly."--BOOK JACKET.
pt. I.A foundation for gerontological practice. A profile of older adults ; The aging network and service providers ; Communication for gerontological practice ; Assessment in gerontological practice -- pt. II. Task-centered practice with the elderly. Initial phase of intervention ; The middle phase ; Final phase : ending service ; Case management ; Practice with caregivers : individuals and groups / Kristina Hash ; Practice in long-term care settings / Debra Lacey -- pt. III. Task planners. Resources and planning ; Home and personal safety ; Living and care arrangements ; Caregiving and respite ; Health and mental health.
Includes bibliographical references (p. [355]-386) and indexes.
Keywords: Social work with older people -- United States; Task-centered social work -- United States; Older people -- Functional assessment; Older people -- Services for -- United States; Older people -- Care -- United States; z; Service social -- z; x; z; x; 2; 2; 2; 2; Service social; 2; 2